COVID-19 and Patient Rights: A Comparative Analysis of Legal Protection Mechanisms at Citra Medika Hospital Indonesia and International Standards - Elvida Sulistiana Sinaga (HM Publisher, 2025)
The COVID-19 pandemic presented unprecedented challenges to healthcare systems globally, highlighting the critical need for robust legal frameworks protecting patient rights. This study investigated the legal protection mechanisms for COVID-19 patients at Citra Medika Hospital, Indonesia, comparing them with international standards. This empirical legal study employed a descriptive approach. Data collection involved a comprehensive review of hospital regulations, national laws, and international guidelines. Observations of hospital practices were conducted, and semi-structured interviews were held with hospital staff and COVID-19 patients. Qualitative analysis focused on key patient rights: information, consent, confidentiality, second opinions, and access to medical records. Citra Medika Hospital demonstrated efforts to protect patient rights, including informed consent procedures, confidentiality protocols, and provisions for accessing medical records. However, gaps were identified concerning the clarity and accessibility of patient information and the practical implementation of the right to a second opinion. In conclusion, while Citra Medika Hospital has established some mechanisms to protect patient rights during the COVID-19 pandemic, further enhancements are needed to align with international best practices. Recommendations include improving patient information materials, strengthening procedures for second opinions, and enhancing staff training on patient rights.